"DIFFICULT AIRWAY MANAGEMENT IN A PATIENT WITH TREACHER-COLLIN’S SYNDROME WITH INTUBATING LARYNGEAL MASK AIRWAY " - M. Gharebaghian (Acta Medica Iranica, 2006)
Treacher Collin’s syndrome (TCS) is a rare inherited condition characterized by bilateral and symmetric abnormalities of structures within the first and second bronchial arches. Patients with TCS present a serious problem to anesthetists maintaining their airway as upper airway obstruction and difficult tracheal intubation due to severe facial deformity. Because of retrognathia, airway management of these patients is often challenging. We report the case of a 25-yr-old patient with TCS undergoing microtia repair under general anesthesia twice. In the first time he could not be intubated via direct laryngoscopy and was intubated via blind nasal intubation. In the second time, he was intubated through an ILMA using endotracheal tube.